Students’ Engagement in Text-to-Speech Based Listening Materials Incorporating Local Wisdom and Religious Values - Indasari, Nur Laili; Srinio, Fuad; Ryandini, Elda Yulia; Rosyidi, Ali; Fitriyah, Rohmatul (At-tadzkir: Islamic Education Journal, 2025)
This study explores students’ engagement during the implementation of developed listening materials by utilizing a text-to-speech (TTS) application, focusing on three key aspects: behavioral, emotional, and cognitive engagement. Employing a quantitative research design, the study involved 120 students from four Madrasah Aliyah schools in Gresik, Indonesia. Data were collected through a questionnaire adapted from Fredricks et al. (2004) and analyzed using descriptive statistics. The findings revealed that the majority of students (51%) were neutral regarding the local wisdom and religious-value-based listening materials, indicating limited cognitive engagement among students. Emotional engagement was the most prominent, with 40% of students feeling more motivated and connected to the content, indicating the cultural and religious relevance resonated well. For the aspect of behavioral engagement, most students (50.20%) also remained neutral, suggesting that even though the materials were acceptable, this approach did not sufficiently stimulate greater active involvement in the learning process. These findings highlight that while students appreciated the cultural and religious relevance, technical limitations of TTS may have impeded deeper learning involvement. This research contributes to English as a foreign language pedagogy by emphasizing the importance pairing culturally grounded materials with interactive strategies and improved TTS quality to enhance engagement more holistically.